Addressing Multimorbidity to Improve Healthcare and Economic Sustainability. Issue 1 (2016) - Colombo, Francesca; García-Goñi, Manuel; Schwierz, Christoph
Patients with multimorbidity are responsible for more than half of all healthcare utilization, challenging the healthcare budgets of all European nations. Although the European Union is showing signs of a fragile economic recovery, achieving sustainable growth will depend on delivering a combination of fiscal responsibility, structural reforms, and improved efficiency. Addressing the challenges of multimorbidity and providing more effective, affordable, and sustainable care, has climbed the political agenda at a global, European, and national level. Current healthcare systems are poorly adapted to cope with the challenges of patients with multimorbidity. Little is known about the epidemiology and natural history of multimorbidity; the evidence base is weak; clinical guidelines are not always relevant to this population; and financing and delivery systems have not evolved to adequately measure and reward quality and performance. Pockets of innovation are, however, beginning to emerge. In Spain, for example, the ongoing economic crisis has forced regional governments to deliver substantial efficiency savings and, with this in mind, integrated care programmes have been introduced across the country for people with chronic disease and multimorbidity. Early results suggest that formalized integrated care for patients with multimorbidity improves their perceptions of care coordination, reduces hospital and emergency admissions and readmissions, and reduces average costs per capita. Such innovations require meaningful investments at a national level – something that is now supported within the framework of the European Union's Stability and Growth Pact.